PERBANDINGAN ALOKASI PENEMPATAN FILTER AKTIF DAN FILTER PASIF UNTUK MENDAPATKAN DISTORSI DAYA TERKECIL PADA JARINGAN DISTRIBUSI DI BLUE POINT BAY - Auryn Herman Gautama; Antonius Ibi Weking; I Wayan Rinas (Program Studi Teknik Elektro UNUD, 2020)
Harmonic filter is a power electronics technology to produce specific current components that canbe used to reduce harmonic currents generated by non-linear loads. Non-linear load is usually foundon electronic equipment in which there are semi-conductor components, such as the use of airconditioners, TVs, computers, medical equipment, musical instruments and so forth. Based onpreliminary measurements at Blue Point Bay Villa & Spa, the simulation results of the THD (TotalHarmonic Distortion) current value of 25.17%, which means exceeding the IEEE 159-2014 standardvalue of ? 15.0%. Filters that are placed incorrectly can cause THD harmonics to be suboptimal. Fromthe results of the study it was found that the THDv value at Blue Point Bay Villa & Spa was 4.83%where these conditions met the maximum THDv IEEE 519-2014 standard for voltages ? 69 kV. THDivalue at Blue Point Bay Villa & Spa after the use of active and passive filters is ? 15% and accordingto IEEE Standard 519-2014. The best placement of active filters to reduce power distortion is SDP 2.2because it can reduce power distortion from 20.08% to 3.94%, and the best passive filter placement isMDP 2, because it can reduce power distortion from 20.13 % to 8.52%.